Urban energy transitions and rural income generation: Sustainable opportunities for rural development through charcoal production. (January 2019) - Smith, Harriet Elizabeth; Jones, Daniel; Vollmer, Frank; Baumert, Sophia; Ryan, Casey M.; Woollen, Emily; Lisboa, Sá N.; Carvalho, Mariana; Fisher, Janet A.; Luz, Ana C.; Grundy, Isla M.; Patenaude, Genevieve
Highlights: Rural charcoal producers were heterogeneous in production scales and demographic characteristics. The size of the urban market affects both the type of rural producer and their scales of production. Rural producers were highly dependent on charcoal income, contributing 38–95% of total gross household income. Small-scale producers were proportionally the most dependent on charcoal income. The existence of households 'trapped' in low production may be a consequence of larger urban markets. Abstract: Sub-Saharan Africa's charcoal sector is rarely considered a mechanism for rural development or poverty alleviation; instead, current regulations often marginalise rural producers. The development of a sustainable sector, that does not further marginalise rural populations, is restricted by limited understanding of these stakeholders. We assess the heterogeneity of rural producers supplying two differentially sized urban charcoal markets in Mozambique. Drawing on data from 767 household surveys, our findings suggest that the size of the urban market affects the type of rural producer and their scales of production. Overall household income of producers supplying the larger urban market were proportionally more dependent on charcoal for income generation; small-scale producers in particular relied most on charcoal income, contributing >95% of household incomes. In contrast, producers supplying the smaller market had more diversified incomes, and were thus less dependent on charcoal income. Larger-scale producers were generally wealthier; their absolute incomes were higher and they were proportionally the least dependent on charcoal income. Further findings suggest that rural charcoal production was not necessarily the domain of the poorest of the poor and the existence of producers trapped in small-scale production may be a consequence of larger urban markets, rather than an intrinsic characteristic of the sector. Predicted growth of smaller urban areas and associated higher demand for charcoal will provide substantial opportunities for rural income generation, most likely leading to shifts in producers and production scales. Rather than transferring existing formal approaches, which marginalise rural stakeholders, small urban areas provide opportunities to develop equitable production systems, with potential to deliver sustainable energy and rural development. The heterogeneity of rural producers calls for better-targeted interventions that incorporate the importance of charcoal production for rural livelihoods.